IMPROVING STUDENTS’ PROBLEM SOLVING ABILITIES THROUGH INQUIRY LEARNING MODELS - Nurmauli br Harianja (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to improve students' problem solving ability. For this reason, teachers were required to create learning that accommodated the stages to achieve learning objectives in the form of drawing conclusions through hypotheses and data collection. One of the appropriate learning models for this purpose was inquiry learning. This study was conducted in class VI B of SDN 9 Mandau and carried out from March to April 2019. The method used in this study was classroom action research, which included the stages of planning, implementation, observation, and reflection. The instrument used in this study was observation sheets. The results revealed that the students’ problem solving ability in the first cycle was 73.37 with a total classical completeness of 62.96%, in which only 17 students reached the KKM. In cycle II, the students' problem solving ability increased to 81.01 and the total classical completeness reached 92.59%, meaning that 25 students achieved the predetermined KKM. Based on these results, it was concluded that the inquiry learning model improved students’ problem solving abilities in grade VI B of SDN 9 Mandau.